Nuclear Import Analysis of Two Different Fluorescent Marker Proteins into Hepatocyte Cell Lines (HuH-7 Cell) - Aris Haryanto; Michael Kann (Universitas Gadjah Mada, 2005)
The application of fluorescent proteins as expression markers and protein fusion partners has proved immensely valuable for resolving the organization of biological events in living cells. EGFP and DsRed2 are commonly fluorescent marker protein which is used for biotechnology and cell biology research. The present study was designed to identify the expression vector that suitable to ligate with DNA encoding HBV core protein for intracellular localization study in hepatocyte cell, which were expressed as fusion proteins. We also compared and quantified the expressed fluorescent protein which predominantly localized in the cell compartment. The results indicated that DsRed2 shown as less than ideal for intracellular localization study of than EGFP, because of its tetrameric structure of the fluorescent protein and when fused to a protein of interest, the fusion protein often forms aggregates in the living cells. In contrast, EGFP fluorescent protein shown a much higher proportion of cytoplasmic localization, thus being more suitable for analysis of intracellular localization than DsRed2 fluorescent protein. EGFP fluorescent protein is also capable to produce a strong green fluorescence when excited by blue light, without any exogenously added substrate or cofactor, events inside living cell can thus be visualized in a non-invasive way. Based on our present quantitative data and some reasons above shown that EGFP is more suitable than DsRed2 as a fluorescent marker protein for intracellular localization study into HuH-7 cell.